Children’s attitudes towards water: a scale development study - Aysu, Burçin; Aral, Neriman; Aydoğdu, Fatih; Gürsoy, Figen (Frontiers in Education, 2025)
IntroductionIn this study, it was aimed to develop a scale to determine children’s attitudes towards water.MethodsThe study included 865 children studying in the fourth to eighth grades. The items of the scale were formed based on the theoretical structure, a comprehensive review of existing scales related to attitudes towards water and expert evaluations. Content validity, exploratory factor analysis, confirmatory factor analysis and reliability analyses were performed from psychometric analyses to determine the validity and reliability features.ResultsAs a result of the study, a scale consisting of three factors (water cycle, importance of water, water saving) and 24 items with acceptable validity and reliability values was obtained.DiscussionThe scale has reliable psychometric properties and can be used as an important assessment tool in evaluating children’s attitudes towards water.